MoC based Mott–Schottky electrocatalyst for boosting the hydrogen evolution reaction performance. Issue 1 (14th November 2019) - Ji, Xinyang; Wang, Kaixuan; Zhang, Yao; Sun, Haohao; Zhang, Yuanyuan; Ma, Tiange; Ma, Zhuo; Hu, PingAn; Qiu, Yunfeng
Abstract : Searching for promising HER electrocatalysts is an urgent task for the practical application of hydrogen production by water electrolysis. Abstract : Searching for promising HER electrocatalysts is an urgent task for the practical application of hydrogen production by water electrolysis. The Mott–Schottky effect between a metal with larger work function and n-type semiconductor with a higher Fermi level will facilitate the electron transfer from the semiconductor toward the metal. As a result, it is possible to design optimal H* adsorption active sites with thermoneutral hydrogen adsorption free energy (Δ G H* ). Herein, MoC nanoparticles with a diameter of about 3.4 nm embedded in N, P-codoped carbon were converted from well-defined polyoxometalates (around 1 nm) and polypyrrole nanocomposites by carbonization and further wrapped on the surface of CNTs. On the basis of improved electron transfer rate, increased carrier densities, and enhanced active site activities on MoC after lowering the work function due to the Mott–Schottky effect with n-type domains in N, P-codoped carbon, our electrocatalysts could drive the current density of 10 mA cm −2 at 175 mV with a Tafel slope of 62 mV dec −1 and TOF value of 1.49 s −1 at 150 mV, as well as long-term H2 production stability. The present study provides a new guideline for the design and preparation of Mott–Schottky HER electrocatalysts.